Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
[tex]f^{-1}(x)= \frac{3}{2}(x+6)[/tex]
[tex]f(f^{-1}(x)) = f^{-1}(f(x))= x[/tex]
Step-by-step explanation:
Given
[tex]f(x) = \frac{2}{3}x - 6[/tex]
Required
Determine [tex]f^{-1}(x)[/tex]
[tex]f(x) = \frac{2}{3}x - 6[/tex]
Represent f(x) as y
[tex]y=\frac{2}{3}x - 6[/tex]
Swap the positions of x and y
[tex]x=\frac{2}{3}y - 6[/tex]
Add 6 to both sides
[tex]x+6=\frac{2}{3}y - 6+6[/tex]
[tex]x+6=\frac{2}{3}y[/tex]
Multiply both sides by 3
[tex]3(x+6)=\frac{2}{3}y * 3[/tex]
[tex]3(x+6)=2y[/tex]
Divide both sides by 2
[tex]\frac{3}{2}(x+6)=\frac{2y}{2}[/tex]
[tex]\frac{3}{2}(x+6)=y[/tex]
[tex]y= \frac{3}{2}(x+6)[/tex]
Replace y with [tex]f^{-1}(x)[/tex]
[tex]f^{-1}(x)= \frac{3}{2}(x+6)[/tex]
Justify the result:
First, we solve for [tex]f(f^{-1}(x))[/tex]
[tex]f(x) = \frac{2}{3}x - 6[/tex]
[tex]f(x) = \frac{2}{3}x - 6[/tex] becomes
[tex]f(f^{-1}(x)) = \frac{2}{3}x - 6[/tex]
Substitute [tex]\frac{3}{2}(x + 6)[/tex] for x
[tex]f(f^{-1}(x)) = \frac{2}{3}(\frac{3}{2}(x + 6)) - 6[/tex]
[tex]f(f^{-1}(x)) = \frac{2*3}{3*2}(x + 6)- 6[/tex]
[tex]f(f^{-1}(x)) = \frac{6}{6}(x + 6)- 6[/tex]
[tex]f(f^{-1}(x)) = 1*(x + 6)- 6[/tex]
[tex]f(f^{-1}(x)) = x + 6- 6[/tex]
[tex]f(f^{-1}(x)) = x[/tex]
Next, we solve [tex]f^{-1}(f(x))[/tex]
[tex]f^{-1}(x)= \frac{3}{2}(x+6)[/tex]
[tex]f^{-1}(x)= \frac{3}{2}(x+6)[/tex] becomes
[tex]f^{-1}(f(x))= \frac{3}{2}(x+6)[/tex]
Substitute [tex]\frac{2}{3}x - 6[/tex] for x
[tex]f^{-1}(f(x))= \frac{3}{2}(\frac{2}{3}x) - 6+6[/tex]
[tex]f^{-1}(f(x))= \frac{3}{2}(\frac{2}{3}x)[/tex]
[tex]f^{-1}(f(x))= \frac{2*3}{3*2}x[/tex]
[tex]f^{-1}(f(x))= \frac{6}{6}x[/tex]
[tex]f^{-1}(f(x))= 1*x[/tex]
[tex]f^{-1}(f(x))= x[/tex]
Hence:
[tex]f(f^{-1}(x)) = f^{-1}(f(x))= x[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.